COMPARATIVE CHARACTERISTICS OF THE CARBOHYDRATE RESIDUES ON THE STRUCTURAL COMPONENTS OF THE TERMINAL SECRETORY DEPARTMENTS OF THE SUBMANDIBULAR SALIVARY GLANDS OF MAN AND SOME LABORATORY ANIMALS - Білаш, В.П. (World of Medicine and Biology, 2016)
Work with lectinocytochemical studies a comparative analysis of the composition of carbohydrate residues on the structural components of the end divisions of the submandibular salivary glands of man and involving laboratory animals: dog, rabbit, rat, Guinea pig. Established that the distribution of carbohydrate residues on the structural components of the end divisions of the submandibular salivary glands depends on the species of origin of an individual and has their similar and different characteristics.